The Java developers alamanac 1999 - Chan, Patrick 1961- (Java series., 1999)
Revered for his annotations and examples of the Java class libraries, Patrick Chan brings his unparalleled knowledge of the class libraries and the core packages together with his mastery of information organization to create The Java Developers Almanac. First issued in 1998, the Almanac is back covering the final customer ship release of The Java Development Kit JDK1.2. All Java programmers will benefit from this comprehensive, accurate, and timely guide that distills the many z new features incorporated into the most current release. The Almanac provides a snapshot description of all of the packages, classes, methods, and interfaces, full of interesting facts and features of the language. A popular section gives historical analysis of development of Java, listing details on the various versions of the JDK, helping programmers to better manage compatibility of their applications. The book supports all versions of the JDK, from 1.2 down to 1.0. - See more at: http://www.betterworldbooks.com/the-java-developers-almanac-1999-id-0201432986.aspx&utm_source=Affiliate&utm_campaign=Text&utm_medium=booklink&utm_term=3630151&utm_content=Homepage#sthash.liKYZhi4.dpuf